Reliability analysis of circular reinforced concrete columns subject to sequential vehicular impact and blast loading. (1st August 2018) - Thomas, R.J.; Steel, Kylie; Sorensen, Andrew D.
Highlights: Reliability of circular columns under sequential impact and blast loading is studied. Reliability is most sensitive to column diameter and blast standoff distance. Fault tree analysis for blast sequential loading is neither convenient nor practical. Residual strength factors show promise in accurately representing reliability. Abstract: This study investigates the first-order second-moment structural reliability of circular reinforced concrete (RC) bridge columns subjected to vehicular impact, explosive blast, and sequential vehicular impact and explosive blast loading. The analysis is performed for five vehicle types of increasing size, mass, and explosive charge capacity. The structural reliability under vehicular impact is shown to be highly sensitive to column diameter, reinforcement ratio, and vehicle velocity. The structural reliability under explosive blast loading is shown to be highly sensitive to column diameter, reinforcement ratio, and blast standoff distance. In general, the structural reliability is lower under explosive blast loading. The structural reliability under sequential loading is evaluated by the newly proposed resistance reduction method and by fault tree analysis. A resistance reduction factor for the second event is defined as a function of the probability of failure under the first event. The resistance reduction method is shown to be more conservative than fault tree analysis and has the added benefit of allowing for the derivation of the density function for performance under sequential loading.